"Seelenbeschreibungen" Eine frühneuzeitliche Quellengattung und ihr konfessions- und bildungsgeschichtlicher Kontext - Schmidt, Heinrich Richard; Albrecht-Birkner, Veronika; Egger, Michael; Ehrenpreis, Stefan; Scheurer, Janine (Konfession und Literalität in der Vormoderne / Confession and Literacy in the Pre Modern Era, 2022)
This volume examines an early-modern source "Seelenbeschreibungen" ("descriptions of souls"), the written product of house visits by pastors or elders that were used to measure people's personal religious knowledge. They provide information about catechetical knowledge, familiarity with prayers, and reading and writing competence, providing a unique insight into early modern lifeworlds.